Exploring problem-solving and critical thinking skills of TVET students: an SME employer perspective - Abu Kasim, Affizie; Mohd Puad, Mohd Hazwan; Abdullah, Arnida (HRMARS, 2024)
The objective of this study is to investigate the perspectives of small to medium enterprise (SME) employers on the problem-solving and critical thinking skills of Technical and Vocational Education and Training (TVET) students during their internships. Recognizing the importance of soft skills in today’s labor market, the researchers aim to identify how practical experience, especially through internships, contributes to the development of problem-solving and critical thinking skills. Using a qualitative case study approach, semi-structured interviews were conducted with three SME employers in the multimedia sector, each with experience supervising TVET students during internships. The thematic analysis of the interview data showed that TVET students problem-solving and critical thinking skills can be developed during the internship programs. Students were able to adapt to the working environment and learn the skills through experience and hands-on practicals. Employers emphasized the need for a more structured approach to fostering these skills, suggesting that continuous exposure to real-world experiences combined with experiential learning in the classroom. However, students still rely heavily on supervision, lack self-confidence in making decisions, and lack creativity, indicating a gap in their preparedness for the workplace. Furthermore, the study highlights the importance of stronger collaboration between TVET institutions and industry. Employers stressed that TVET curricula should be more closely aligned with industry demands to better prepare students for the workforce. The findings suggest that a deeper partnership between educational institutions and industry is crucial to equipping students with the soft skills needed to meet the evolving demands of today’s job market. This study contributes valuable insights for improving TVET programs and enhancing graduate employability.